014 How do musculoskeletal pain, avoidant coping and sickness absence relate to each other?. (16th November 2010) - Christensen, U; Ørsted Hougaard, C; Thielen, K; Nygaard, E; Lund, R
Abstract : Background: Musculoskeletal pain is common and causes extensive sickness absence and work disability in many industrialised countries. The prevalence of musculoskeletal morbidity increases by decreasing socio-economic position and it appears that people with a disadvantaged social situation are more vulnerable to the consequences of musculoskeletal disorders. An avoidant coping strategy has been associated with an increased likelihood of sickness absence, and some evidence has been shown of increasing use of avoidant coping with decreasing social class. Objectives: The objective of this study is to examine the single and joint effect of musculoskeletal pain and avoidant coping on sickness absence and how this effect may be moderated by socio-economic position. Methods: This study was based on a prospective design including survey data from 2000 and 2006 and register data from 2007. The study population consists of a sample of Danes in their 40s and 50s free of major depression at baseline and in 2006, economically active in 2006, and reporting functional limitations due to musculoskeletal pain, N=2967. The outcome measure was retrieved from Statistics Denmark and contained information on sickness absence > 2 weeks in 2007. By multivariate logistic regression the association between self-reported musculoskeletal pain (daily vs weekly/monthly/seldom and never) and sickness absence was studied, adjusted by avoidant coping, physical exposures in work environment, gender and socio-economic position (measured by occupational social class). The joint effect of pain and avoidant coping was calculated as departure from multiplicativity and tested by product terms. Results: The adjusted OR between musculoskeletal pain and sickness absence was 1.76 (95% CI 1.44 to to 2.15). Further analysis showed a departure from multiplicativity for the joint effect of pain and avoidant coping on sickness absence. Socio-economic position had a strong independent effect on the risk of sickness absence (p<0.0001). However, there was no significant moderating effect of socio-economic position on the joint effect of pain and avoidant coping. Conclusion: An avoidant coping strategy interacts with the perception of pain and has a strong effect on the risk of sickness absence. Although socio-economic position is significantly associated with the risk of sickness absence it did not moderate the joint effect of avoidant coping and musculoskeletal pain.